De ontsluiting van het Amsterdamse notariële archief - Reinders, Jirsi (TSEG - The Low Countries Journal of Social and Economic History, 2023)
The archives of the Amsterdam notaries (1578-1915) are an extremely rich but complex source for historical research. Although well known amongst researchers for decades, it was never possible to search the archive completely due to its enormous size (over 3.5 kilometers of shelve length). From 2016 onwards the Amsterdam City Archives have started a renewed attempt to disclosure this archive with new techniques such as crowd sourcing and Handwritten Text Recognition in the project Alle Amsterdamse Akten. This article provides insight in the way the Amsterdam City Archives unlocks the deeds of the seventeenth and eighteenth century notaries and how researchers can benefit from the results of this mass digitization project.